Innovative Management Methods for Patients Allergic to Cats - Leyla S. Namazova-Baranova; Kamilla Y. Efendieva; Julia G. Levina; Elena A. Vishneva; Anna A. Alekseeva; Vera G. Kalugina; Konstantin S. Volkov; Polina S. Arimova; Alina R. Pankova; Anastasiya D. Lamasova (Вопросы современной педиатрии)
The prevalence of allergies to domestic animals increases due to the increase in the number of pets worldwide, followed by serious medical and social problems. Domestic cat (Felis domesticus) is one of the most common pets and one of the most frequent (after dust mite) source of indoor allergens and risk factor for bronchial asthma and allergic rhinitis. This review collects relevant information on the issues of hypersensitivity to cat allergens (the term «cat allergy» will be used later). The authors consider issues of diagnosis, treatment and prevention of this condition. Special attention is given to the management of patients with cat allergies and particularly usage of special nutrition for cats that can reduce the level of the main cat allergen Fel d 1 in the environment. Whereas, this leads to decrease of allergic diseases symptoms severity.